Diseño de estrategias de vacunación contra la Coriza Infecciosa en pollitos de engorde de un día de vida - Cigoy, María Luciana (2023)
Infectious Coryza (IC) is a bacterial disease distributed worldwide and caused by Avibacterium paragallinarum, a bacterium affecting the upper respiratory tract of Gallus gallus. Clinical signs may spontaneously subside after a week, although it is commonly associated with other pathogenic agents that may worsen the disease and prolong its course. It has been mainly studied in laying hens, because the disease decreases the production of eggs. In broilers IC usually occurs as a subclinical infection and may cause economic losses due to growth retardation and condemnations, particularly when Av. paragallinarum is associated with other viral or bacterial agents. Infections may be underdiagnosed, due to the difficulties to isolate the pathogen, which requires cultural and incubation conditions that are not always available in all diagnostic laboratories. Vaccination is the main prophylactic tool, although only breeders and laying hens are vaccinated by parenteral administration of bacterins. In contrast, broilers are not vaccinated because handling maneuvers of birds to give parenteral booster doses could negatively impact on the weight gain. Therefore, the aim of this Thesis was to design vaccination strategies for controlling IC in broiler chickens by giving a single dose at the 1st day of life. An enriched broth was formulated allowing to yield Av. paragallinarum in the range of 108 CFU/L. Two independent trials were performed, in which birds were immunized at the 1st day of life and thereafter challenged by injection into one infraorbital sinuses at the 30th day of life. Firstly, the outcome of separately injecting both adjuvants, alone or combined with antigens, was evaluated in a model of persistence of infection achieved with low challenge doses of Av. paragallinarum (104 CFU/bird). There were no significant differences among the isolation rates of the pathogen or the clinical symptoms of the disease, showing that no deleterious effects related to the use of adjuvants were registered. Using an infection model of higher challenge doses (105 CFU/bird) another trial was carried out to evaluate protection by comparing bacterins routes. The efficacy of three vaccination strategies was evaluated: ocular instillation, subcutaneous injection and simultaneous administration by both routes. There were no significant differences among the weights of the birds from the different experimental groups, including the unchallenged control group, suggesting that handling of birds to carry out vaccination at the first day of life, did not affect the subsequent weight gain. Moreover, no deleterious effects were caused by the adjuvants or the bacterins. Vaccination at the first day of life in broilers was shown to be effective when the ocular instillation dose was administered together with the subcutaneous injection. This strategy of double vaccination route, provided a high protection rate (77.8%) and only 22.2% of Av. paragallinarum isolation rates from sinuses could be recorded, together with a remission of the typical lesions of the disease, which ranged from an initial 55.6% up to nil at the 7th day post-challenge. In contrast, chicks that were only vaccinated by ocular instillation or by subcutaneous route were not protected and high Av. paragallinarum isolation rates were recorded. Determination of HI antibody titers were not possible, although the presence of agglutinating antibodies in serum was detected by microplate agglutination. The results of this Thesis proved that broiler chicken protection against IC, through vaccination at the 1st day of life, could be afforded by giving simultaneously ocular and subcutaneous bacterins. This broiler immunization strategy at the 1st day of life, could be used in hatcheries and also may be extended to laying hens and breeders, in order to protect birds from birth and to reduce constant reinfections that frequently occur when new flocks of birds are introduced and get infected by resident birds.